The cheerleaders - Thomas, Kara, 1990- (Delacorte Press, 2018)
"There are no more cheerleaders in the town of Sunnybrook. First there was the car accident--two girls dead after hitting a tree on a rainy night. Not long after, the murders happened. Those two girls were killed by the man next door. The police shot him, so no one will ever know his reasons. Monica's sister was the last cheerleader to die. After her suicide, Sunnybrook High disbanded the cheer squad. No one wanted to be reminded of the girls they'd lost. That was five years ago. Now the faculty and students at Sunnybrook High want to remember the lost cheerleaders. But for Monica, it's not that easy. She just wants to forget. Only, Monica's world is starting to unravel. There are the letters in her stepdad's desk, an unearthed, years-old cell phone, a strange new friend at school. . . . Whatever happened five years ago isn't over. Some people in town know more than they're saying. And somehow, Monica is at the center of it all. There are no more cheerleaders in Sunnybrook, but that doesn't mean anyone else is safe."--